Financial management of patients infected with SARS-CoV-2 virus in Romania - Blebea, Nicoleta; Mitea, Gabriela (Technium Business and Management, 2022)
In this article, we highlight comprehensive and up-to-date information on the analysis of the central public administration that addresses how the authorities, institutions and central public entities with responsibilities in preventing and combating the spread of the COVID-19 pandemic in Romania have used public funds allocated in this purpose. Romania has accepted the decrease of budget revenues, through a series of fiscal measures and by diminishing the income-generating economic activities. The budgets of some main authorizing officers with special attributions during the state of emergency were supplemented, namely: the Ministry of Labor and Social Protection; Ministry of Health; Ministry of Public Finance; Ministry of Public Works, Development and Administration; Ministry of Interior; Ministry of Transport, Infrastructure and Communications; Ministry of Agriculture and Rural Development; Public ministry; National Sanitary Veterinary and Food Safety Authority; Special Telecommunications Service; Romanian Information Service; Ministry of Foreign Affairs; Romanian Academy. In order to implement measures to prevent and combat the pandemic, as well as to manage the state of emergency, a series of resources were mobilized, in addition to donations and sponsorships, received by public institutions from the central public administration during the state of emergency. At the same time, for the local government component, the data are structured in such a way as to reflect the tasks and tasks of local authorities in preventing and combating the pandemic, but also the findings on resource management used for this purpose, segmented into the following areas: medical assistance (medical equipment, medicines, sanitary materials, salary rights, etc.); expenses incurred in establishing the quarantine; disinfection costs imposed by measures to prevent and combat the epidemic; Other expenditure due to the need to take measures to prevent and combat the epidemic. The Government of Romania has adopted an emergency ordinance for the organization and conduct of public information campaigns in the context of the epidemiological situation caused by the spread of COVID-19, in order to raise awareness of the risks of disease and increase voluntary compliance with health and social regulations imposed by competent authorities, in order to limit the spread of the virus after the end of the state of emergency. Audiovisual and printed materials that will be broadcast in public information campaigns, such as audio and video spots, online banners, print mock-ups, mock-ups for billboards, will be created and produced centrally by a creative structure in which specific professional associations can delegate members. from several volunteer and / or paid agencies.